(untitled) (Informatica, 2024)
Different green plant layouts exert crucial impacts on human thermal comfort. The existing green plant layouts in urban streets have not achieved more ideal results in regulating temperature, humidity, and solar radiation. Therefore, in order to design a more livable urban environment, this study analyzes the green plant layout pattern of Street A in a certain city and explores its impact on regional thermal comfort. The study first designs different green plant layouts. Then, the meteorological factors that contribute to the thermal comfort of the region based on an urban microclimate treatment model are analyzed. Finally, the thermal comfort is evaluated using the predicted mean vote-predicted percentage of dissatisfied. The experimental results showed that the average daily predicted mean vote values of the four different simulation schemes were 0.55, 0.71, 0.46, and 0.21, respectively, indicating that shrubs and arbors had a significant regulatory effect on human thermal comfort. There were obvious differences in the improvement effect of different green vegetation arrangements on thermal comfort. The overall improvement effect first increased and then decreased. The designed green vegetation arrangement can more effectively regulate regional microclimate, improve local thermal comfort, and provide a more comfortable and livable working and living environment.